Keeping the customer satisfied: applying a kano model to improve vaccine promotion in the Philippines - Wachinger, Jonas; Reñosa, Mark Donald; Guevarra, Jerric Rhazel; Landicho-Guevarra, Jhoys; Demonteverde, Maria Paz; Silvestre, Catherine; Endoma, Vivienne; Landicho, Jeniffer; Aligato, Mila F.; Bravo, Thea Andrea; Chase, Rachel P.; McMahon-Rössle, Shannon A. (Global health, 2023)
Introduction:The success of global health interventions heavily relies on reaching populations in a way that aligns with their priorities and needs. This warrants novel approaches to determine the design of meaningful interventions and targeted delivery pathways. To date, global health scholarship and practice have largely underused approaches already established in fields that emphasize customer satisfaction, such as quality management or consumer psychology. - Methods:In our study, we apply Kano methodology - originally designed to understand how product attributes nonlinearly influence customer satisfaction - to inform design decisions regarding a video-based vaccine intervention in the Philippines. Between September 2021 and April 2022, we administered a Kano questionnaire to 205 caregivers of small children. Data were analyzed following routine Kano approaches, supplemented by cultural consensus analysis (CCA), which is an approach used largely in anthropology to identify distinct cultural groups and competencies. - Results:Applying Kano and CCA methodologies allowed us to make informed design decisions in terms of optimizing accessibility and credibility of an intervention that ultimately proved successful in bolstering vaccine intentions. Results guided us to include national and international logos, to appreciate the value of summarizing key messages, and to recognize the importance of fact- or story-based communication as attributes that influenced respondent satisfaction one-dimensionally. We found that involving trusted messengers and including text-based information were required to avoid dissatisfaction. Interacting with someone after viewing the product and creating opportunities to share the promotional material via social media were attractive attributes whose presence would increase satisfaction but would not spark severe dissatisfaction if omitted. Other attributes (short duration, video- or animation-based intervention, delivering the intervention at health centers or in group settings) played a limited role in respondent satisfaction. - Conclusions:Global health research and practice can benefit from applying approaches established in other fields when making evidence-based prioritization decisions to tailor interventions.
Gesehen am 04.04.2024